Effect of agarose/gelatin gel addition on the pro-angiogenic potential of polyhydroxybutyrate/chitosan scaffolds - Giretová, Mária; Medvecký, Ľubomír; Demčišáková, Zuzana; Luptáková, Lenka; Petrovová, Eva; Štulajterová, Radoslava (Frontiers in Cell and Developmental Biology, 2025)
The aim of this paper was to evaluate the effect of gel addition to biopolymeric scaffolds on the pro-angiogenic and basic material characteristics of the final composite for use in regenerative medicine. The studied scaffold consisted of natural biopolymers: polyhydroxybutyrate, chitosan, agarose, and gelatin. The final scaffold was characterized by high macroporosity (90%) and wide pore size distribution. As is known, the pore size is a critical factor for cell ingrowth in grafts after implantation in the body and for angiogenic development and creation of new vessels. After 9 days of cultivation in the culture medium, the scaffold retained its physicochemical properties without any tendency of disintegration. The addition of polymeric gels to the scaffold improved the mechanical stability of the composite. In vitro cytotoxicity testing showed good adherence of the seeded L929 fibroblasts on the scaffold and strong ingrowth of cells into the macropores. No sign of cytotoxicity was identified by both the MTS assay and live/dead cell staining. The quail chorioallantoic membrane (CAM) assay—as an alternative to in vivo assays—revealed suitable pro-angiogenic properties of the scaffold for the formation and ingrowth of new blood vessels. Moreover, the upregulation of gene expression responsible for the activation of angiogenic cascade clearly demonstrated a positive effect of the prepared composites on angiogenesis as an essential part of new tissue formation and the regeneration process itself.